Non-melanoma skin cancer essentials for oncologists - Rembielak, Agata (CRC Press, Taylor & Francis Group, 2023)
This book provides a comprehensive introduction to the current state-of-the-art in skin cancer, exploring the recent developments, appraising the current evidence and providing future directions with particular emphasis on interdisciplinary collaboration and need for clinical trials. It covers all aspects of skin cancers, including epidemiology, pathology, surgical and non-surgical treatments. It will be a valuable reference for oncologists, dermatologists, dermatopathologists, surgeons, allied health care professionals and other specialists and trainees with a special interest in skin cancer who want to update their knowledge in the multidisciplinary management of such patients. The book will be of interest to medical physicists and radiographers who would like an overview of the current practice in skin cancer. The book can be used by students in medicine, nursing, radiography and medical physics. Features- Provides a comprehensive review of all aspects of skin cancer management.- Edited by experts in the area, with interdisciplinary and international collaborators. - Promotes a 'Bigger picture' approach to the topic with multidisciplinary insight